Pelatihan Strategi Pemasaran Digital Produk Teh Herbal Seledri - Sukarno Himawan Wibisono; As'adi; Ahmad Mukoffi; Yayuk Sulistiyowati (Studium: Jurnal Pengabdian Kepada Masyarakat, 2023)
The era of the Fourth Industrial Revolution demands that Small and Medium Enterprises (SMEs) like Herbal Celery Tea continuously develop and keep up with technological advancements to remain competitive in marketing their products. Digitalization offers significant opportunities for SMEs to expand their consumer reach and facilitate access to Herbal Celery Tea products, making them more widely known and appreciated by the public. However, to compete effectively, the readiness of human resources in utilizing technology is crucial. Limited understanding of technology poses a major challenge for SMEs in operating the available digital tools and determining appropriate marketing strategies to make their products appealing to consumers. The objective of this community service is to provide understanding to SMEs like Herbal Celery Tea regarding digital product marketing strategies and the importance of proper financial reporting for measuring business performance. Consequently, the desired outcome of this community service is the increase in revenue for Herbal Celery Tea SMEs through the effective implementation of digital marketing strategies and improved financial management.